Airway reversibility in newly developed asthma in children - Ariyanto Harsono; Sri Kusumawardani; Makmuri MS; Gunadi Santosa (Indonesian Pediatric Society Publishing House, 2016)
Objective To determine factors influencing forced expiratory vol- ume in one second (FEV 1 ) reversibility in newly developed asthma in children Methods A cross sectional study was done on 52 patients aged 6- 14 years who were recruited from a longitudinal study of 161 newly developed asthmatic children. Pre and post-bronchodilator FEV 1 were obtained to calculate the reversibility. Seven patients had to perform peak expiratory volume (PEV) variability before recruited. Some variables including sex, age, height, onset of asthma, fre- quency of asthma attacks at the time of the test were analyzed to evaluate their roles in the outcome of FEV 1 reversibility using paired sample t-test, Pearson's correlation coefficient, and multi regres- sion analysis. Results Mean pre- and post-bronchodilator FEV 1 were 1.14 (SD 0.24) and 1.31 (SD 0.28), respectively. FEV 1 reversibility ranged between 6%-36%. Bivariate analyses demonstrated significant cor- relation between either cough (p=0.031) or symptom-free (p=0.041) and the airway reversibility. Multivariate analysis showed that cough was an important factor influencing airway reversibility (p=0.0246). Conclusion Cough is an important influencing factor of the air- way reversibility